1997
DOI: 10.1088/0954-3899/23/12/015
|View full text |Cite
|
Sign up to set email alerts
|

Chemical equilibration of strangeness

Abstract: Abstract. Thermal models are very useful in the understanding of particle production in general and especially in the case of strangeness. We summarize the assumptions which go into a thermal model calculation and which differ in the application of various groups. We compare the different results to each other. Using our own calculation we discuss the validity of the thermal model and the amount of strangeness equilibration at CERN-SPS energies. Finally the implications of the thermal analysis on the reaction … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
81
1
2

Year Published

1998
1998
2003
2003

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(91 citation statements)
references
References 79 publications
7
81
1
2
Order By: Relevance
“…The SSBM analysis for the S+S interaction [15] has shown that this equilibrated state is situated mostly (75%) outside the hadronic phase, whereas the S+Ag [21] is just on the deconfinement line. In addition, the calculations have pointed out a large (∼30%) entropy enhancement of the experimental data compared to the model, an effect observed also by other calculations [23][24][25]. This enhancement may be attributed to contributions from the DQM phase with many liberated new partonic degrees of freedom.…”
Section: Experimental Datasupporting
confidence: 54%
“…The SSBM analysis for the S+S interaction [15] has shown that this equilibrated state is situated mostly (75%) outside the hadronic phase, whereas the S+Ag [21] is just on the deconfinement line. In addition, the calculations have pointed out a large (∼30%) entropy enhancement of the experimental data compared to the model, an effect observed also by other calculations [23][24][25]. This enhancement may be attributed to contributions from the DQM phase with many liberated new partonic degrees of freedom.…”
Section: Experimental Datasupporting
confidence: 54%
“…Several prior attempts have been made to interpret the hadronic particle abundances and spectra within statistical particle production interpretation [2,3,4,5,6,7,8,9], and the present report takes, as we believe it, to a conclusion this extensive body of research work. The result of our present analysis are the parameters and properties of the hadronic system at chemical freeze-out.…”
Section: Introductionmentioning
confidence: 68%
“…G(s, m a , m b ) vanishes at threshold, so that one recovers the tree-level amplitude, and becomes progressively larger with the increase of s, causing an effective suppression of the coupling constant g. At large s, our simple expression shall become inaccurate compared with the solution of the full BS equation with couple-channels effects incorporated, but one should bare in mind that high values of s are exponentially suppressed in the integral that defines the collision rates in Eq. (29). Therefore, this inaccuracy has a small numerical impact in the determination of the collision rates, but is important to avoid artificially large contributions from cross section values above the unitarity limit.…”
Section: B Binary Reactionsmentioning
confidence: 99%
“…The underlying idea is that the equation of state of a gas of free hadrons and resonances should mimic the one of a dense hadron gas [29]. Fig.…”
Section: Time Evolutionmentioning
confidence: 99%